Misaligned incentives and mortgage lending in Asia - GREEN, Richard (Institutional Knowledge at Singapore Management University, 2009)
This chapter provides a conceptual basis for the price discovery potential for tradable market instruments and speciﬁcally the development of mortgage securitization in Asia. We argue that securitization in Asia may be potentially important because it may help bring transparency to the ﬁnancial sector of Asian economies. We put forth a model explaining how misaligned incentives can lead to bank-generated real estate crashes and macroeconomic instability. We provide new comparative data on the banking sector’s performance in Asia compared to the performance of securitized real estate returns, to provide evidence on the potential contribution of misaligned incentives to the magnitude of the declines in the real estate sector in the past. In particular, we show both theoretically and empirically that the banking sector suﬀers relatively low losses following a negative demand shock compared to the losses experienced by the real estate sector. The evidence suggests that the fact that banks’ shares are publicly traded does not discipline the bank lending oﬃcers who are driven by origination fees and market share and does not prevent underpriced lending.